Correlation between plasma and CSF concentrations of kynurenine pathway metabolites in Alzheimer's disease and relationship to amyloid-β and tau - Jacobs, Kelly R.; Lim, Chai K.; Blennow, Kaj; Zetterberg, Henrik; Chatterjee, Pratishtha; Martins, Ralph N.; Brew, Bruce J.; Guillemin, Gilles J.; Lovejoy, David B. (Neurobiology of aging, 2019)
Chronic kynurenine pathway (KP) activation is implicated in Alzheimer's disease (AD) pathophysiology and results in quinolinic acid–induced excitotoxic stimulation of the N-methyl-D-aspartate receptor. However, most studies focus on plasma and it is unclear if peripheral concentrations reflect brain concentrations and how these may correlate to the AD biomarkers amyloid-β, total-tau (t-tau), or phosphorylated-tau (p-tau). We characterized the KP in matched plasma and cerebrospinal fluid (CSF) samples from 20 AD patients and 18 age-matched control subjects. Plasma concentrations of kynurenine (KYN), 3-hydroxykynurenine, anthranilic acid, picolinic acid, and neopterin significantly correlated with their respective CSF levels. In patients with AD, plasma KYN (r = −0.48, p = 0.033) and picolinic acid (r = −0.57, p = 0.009) inversely correlated with CSF p-tau and t-tau, respectively. Furthermore, in AD CSF, increased 3-hydroxykynurenine/KYN ratio correlated with t-tau (r = 0.58, p = 0.009) and p-tau (r = 0.52, p = 0.020). These data support KP involvement in AD pathogenesis and add to the case for the therapeutic modulation of the KP in AD. •CSF KP metabolites correlate with AD biomarkers, t-tau and p-tau.•Kynurenine pathway (KP) metabolites correlate in matched plasma and CSF samples.•KP correlation with t-tau and p-tau may suggest mechanistic links.